Transoral robotic surgery for the treatment of T1–T2 carcinoma of the larynx: Preliminary study. (5th August 2013) - Lallemant, Benjamin; Chambon, Guillaume; Garrel, Renaud; Kacha, Sophie; Rupp, Damien; Galy‐Bernadoy, Camille; Chapuis, Héliette; Lallemant, Jean‐Gabriel; Pham, Huy Trang
Abstract : Objectives/Hypothesis: To determine the feasibility and the preliminary oncological results of transoral robotic surgery (TORS) for the treatment of early stage laryngeal tumors. Study Design: Retrospective single center study. Methods: We reviewed the medical records of 23 patients who underwent TORS for the treatment of T1 or T2 laryngeal squamous cell carcinoma between August 2009 and March 2012. Results: Laryngeal tumors were involving the glottis (13 cases) and the supraglottis (10 cases). They were classified T1 N0 in 16 cases, T2 N0 in four cases, and T2 N+ in three cases. The median TORS operative time was 60 minutes (ranging from 30 to 118 minutes). The median hospitalization time was 7.5 days. Histopathological examination of the resected tumors confirmed 14 cases in which the margins were clear, four cases in which the surgical margins were close (less than 1 mm), one case in which the margins were microscopically positive, and in four cases margins status were not able to be recorded. A tracheostomy was carried out for three patients, and 11 patients got a nasogastric feeding tube postoperatively. The local recurrence rate was 8.7% (2/ 23 cases), and in both cases the recurrence occurred in the anterior commissure area only. The overall larynx preservation rate was 95, 7% (22/ 23 cases). Conclusion: In this preliminary study, we demonstrated that laryngeal TORS is feasible and may result in oncological results comparable with other treatment strategies, including laser CO2 surgery. This innovative approach needs to be evaluated through randomized multi‐institutional trial. Level of Evidence: 4. Laryngoscope, 123:2485–2490, 2013